"Counselors Change, Too": A Phenomenological Inquiry of Experienced-Counselors’ Spiritual Experience through Counseling Relationship - Kim, Sinae (Counseling and values, 2023)
In this phenomenological study, the authors explored the lived experiences of seven experienced Korean counselors’ spiritual changes and growth through their counseling relationship. Three semi-structured interviews were conducted with each participant. Using an iterative process, the findings were categorized into six themes and 14 sub-themes. Six themes include believing in clients and loving them, appreciating their relationship with God, finding meaning in life, accepting the client as teacher, feelings of being connected, and recovering after experiencing limitations. Implications for how spirituality can be utilized in counseling and counseling education were presented.